A Study of Social Health Status in the Population of the Prospective Epidemiological Shahrekord Cohort Study in Chaharmahal and Bakhtiari Province in 2019 - Maryam Sadat Ghaemfard; Ali Ahmadi; Asieh Mansouri; Soleiman Kheiri (Shahrekord University of Medical Sciences, 2021)
Background and aims: Social health refers to the quantity and quality of interaction of an individual with society to promote the well-being of individuals in the society. This interaction promotes social capital and social security, and reduces poverty and injustice. So far, no study has been ever done on the social health situation in Chaharmahal and Bakhtiari province. This study aimed to investigate the social health status in Chaharmahal and Bakhtiari province in 2019.   Methods: In this cross-sectional and descriptive-analytical study, the data from the prospective epidemiological study of Shahrekord cohort study in Chaharmahal and Bakhtiari province in 2019 were used. In order for measuring social health, a valid Iranian social health questionnaire with a score range of 33-165 was used. ANOVA and t test in SPSS version 22 were employed for analyzing the data in order to compare the mean values.   Results: By way of explanation, 597 individuals out of 600 samples completed the social health questionnaire (99.5% response rate). The mean ± standard deviation age of participants was 48.54±9.33 years and the mean ± standard deviation score of their social health was 115.71±22.7. This score was higher in men than in women (P = 0.038). Social health score was significantly higher in urban areas than in rural areas (P = 0.001). Social health was highest in civil servants, and lowest in unemployed participants (P = 0.001). Social health score was lower in obese and high body mass index (BMI) individuals than in normal BMI individuals (P = 0.047).   Conclusion: Social health in the studied population was moderate and, therefore, deserves the attention of health policy makers and planners. Social health can be improved by holding training classes for villagers and teaching them how to interact with each other - especially with family members, furthering participation of women in social affairs and increasing their social relationships, giving advice on diets and social health to people with non-normal BMI, as well as by holding post-retirement training classes for retirees.